Therapeutic Plasma Exchange pada Pasien dengan Sindrom Guillain–Barré - EVANS P. BIASA; MORDEKHAI L. LAIHAD; BARRY I. KAMBEY (Universitas Hang Tuah, 2026)
Abstract Guillain–Barré Syndrome (GBS) is an acute autoimmune neuropathy that may rapidly progress to severe weakness and respiratory failure. Therapeutic plasma exchange (TPE) is a recommended immunomodulatory therapy, particularly in patients with severe clinical manifestations. Case Report: We report a 64-year-old female presenting with rapidly progressive quadriparesis requiring intensive care and mechanical ventilation. Nerve conduction studies confirmed Guillain–Barré Syndrome, Acute Motor and Sensory Axonal Neuropathy (AMSAN) subtype. The patient underwent four cycles of therapeutic plasma exchange. Although standard protocols generally recommend five cycles, treatment was discontinued earlier due to significant clinical improvement. Discussion: Following TPE, the patient demonstrated gradual clinical improvement, including hemodynamic stabilization, reduced ventilatory support, and successful extubation. This rapid clinical response supports an individualized approach to determining the number of TPE cycles based on continuous clinical evaluation, particularly in critically ill patients in the intensive care unit. Therapeutic plasma exchange may serve as an important immunomodulatory therapy in patients with severe Guillain–Barré Syndrome. Individualizing the number of TPE cycles based on clinical response can be considered in clinical practice without strict adherence to standard protocols. This case highlights that serial clinical evaluations may serve as a basis for considering individualized TPE cycle numbers in severely ill GBS patients in the intensive care unit.